Short‐term and long‐term unstimulated saliva flow following unilateral vs bilateral radiotherapy for oropharyngeal carcinoma. Issue 2 (15th October 2020) - Huang, Shao Hui; de Almeida, John R.; Watson, Erin; Glogauer, Michael; Xu, Wei; Keshavarzi, Sareh; O'Sullivan, Brian; Ringash, Jolie; Hope, Andrew; Bayley, Andrew; Bratman, Scott V.; Cho, John; et al.
Abstract: Background: We aimed to compare unstimulated saliva flow using 3‐minute modified Schirmer test (MST) following bilateral vs unilateral radiotherapy (RT) in oropharyngeal carcinoma (OPC). Methods: We reviewed OPC patients treated with definitive intensity‐modulated radiation therapy (IMRT) between 2011 and 2017. MST was measured at baseline, 1‐/6‐/12‐/24‐month post‐RT. MST values were compared between bilateral‐RT vs unilateral‐RT groups. Multivariable logistic regression analysis (MVA) identified predictors of hyposalivation (MST < 25 mm). Results: Total 498 bilateral‐RT and 36 unilateral‐RT patients were eligible. The MST values at 1‐/6‐/12‐/24‐month post‐RT were all significantly reduced from baseline for the entire cohort. Baseline unilateral‐RT and bilateral‐RT MST values (in mm) were similar ( P = .2), but much higher for unilateral‐RT 1‐month (mean: 19.1 vs 13.0, P = .03), 6‐month (20.5 vs 9.3, P  < .001), 12‐month (20.1 vs 11.9, P  < .01), and 24‐month post‐RT (22.2 vs 13.9, P = .04). MVA confirmed that unilateral RT reduced the likelihood of hyposalivation vs bilateral RT (OR 2.36, P = .006). Conclusion: Unilateral RT reduces unstimulated salivary flow in OPC patients.